Is Public Procurement a Successful Small Business Support Policy? A Review of the Evidence. (February 2013) - Loader, Kim
Public procurement is a vehicle by which governments can provide direct support to small business. The public sector market is significant and attractive to suppliers of all sizes, yet the current UK government is the latest to feel the need to implement a variety of measures in an attempt to improve the chances of success for smaller suppliers. In this context I have undertaken a critical review of the existing evidence relating to this issue. I have found support for the policy to encourage small and medium-sized enterprise suppliers but also that many barriers, some first identified twenty years ago, still remain. Whilst various remedies have been proposed, it appears that public procurers lack clear priorities and objectives. This, together with a lack of regular and comprehensive supply data, is hindering improvement.